PENGARUH DIGITAL INFLUENCER DAN ENDORSEMENT TERHADAP KEPUTUSAN PENGGUNAAN TABUNGAN SYARIAH OLEH GEN Z (Studi Kasus Mahasiswa FEBI UIN STS Jambi ) - Badriah Badriah; Titin Agustin Nengsih (MARGIN: Journal of Islamic Banking, 2025)
This study examines the influence of digital influencers and endorsements on Generation Z's decision to use Islamic savings accounts. The research background is based on the increasing interest of Gen Z in Islamic banking services and the role of digital marketing in shaping consumer decisions. The objective of this study is to analyze the extent to which digital influencers and endorsements contribute to the decision to save in Islamic banks. This research employs a quantitative approach with a survey technique, involving students from the Faculty of Islamic Economics and Business at UIN Sulthan Thaha Saifuddin Jambi as respondents. Data analysis was conducted using multiple linear regression to examine the relationship between variables. The findings indicate that both digital influencers and endorsements have a significant impact on the decision to use Islamic savings accounts, both partially and simultaneously. These results confirm that effective digital marketing strategies can enhance Gen Z's awareness and interest in Islamic banking products.